TUTURAN PENGAJAR BAHASA INGGRIS DALAM KELAS DI LEMBAGA KURSUS LIA HARAPAN INDAH : SUATU KAJIAN ANALISIS WACANA KRITIS - Dea Gemilang Sashi; Heri Yusup (Fakultas Komunikasi, Sastra, dan Bahasa, 2015)
Utterance is product of verbal act which is formed in a sentence, composed by words and phrases and delivered orally from speaker to hearer in a situational context. Every utterance is an act that manifests power of the speaker. By doing a research in LIA Harapan Indah, I propose to have research to analyze power’s manifestation of a teacher through his/her utterances in classroom. By using three dimensions theory of Critical Discourse Analysis by Norman Fairclough, the data results show that in Elementary classes, teachers show overt power. On the other hand, in Intermediate, High Intermediate and Conversation classes, teachers show covert power